La Tinaia : Ein Werkstattbuch über die Cooperativa di attività espressive, La Tinaia. - Mensi, Massimo; Nabholz, Beatrice; Duttweiler, Catherine; Eissing-Christophersen, Christoph; Réja, Marcel; Gercken, Günther (Zürich : Baumann & Stromer, 1991)
Gelli, Giordano ; Trinchera, Gabriele ; Boni, Guido ; Raugei, Marco ; Pastore, Giuseppina ; Settembrini, Franca ; Paoli, Paolo ; Rafanelli, Paolo ; Ulivieri, Claudio ; Motolese, Francesco
Duits
kunstcatalogus